An Analysis of the Concepts for Organization and Arranging with Furniture of Office Spaces - Aziri, Zejnelabedin; Nikoljski Panevski, Elena (Scientific Foundation Spiroski (publications), 2016)
With this paper it is made an analysis of the concepts for organization of the furniture and furnishing of office spaces. Two different aspects are beeing developed, which are intended for two different business structures and entities. The comparative approach for two functional divergent concepts allows clearer insight in the requests, the possibilities and the capacities of the premise for each specific purpose. Through the project analyzes the potential users of the office space would have detailed review and knowledge for the planning and the design procedures of the concrete space. The organization of the furniture and the remaining arrangement vary in the two project varieties created for them and are much depended on analyses of the anthropometric and ergonomic principles of design being applied in the development of the project varieties. This analysis is made through strategic planning of the office space. With this analysis the users of the office space would have detailed overview of the space in which they should work the arrangement of the furniture and other inventory and also of the way the employees are being arranged in the company and what conditions are provided to them. Also there is a short overview of the ergonomic principles that can be applied. With this method a detailed analysis is provided over the concepts for the organization and furnishing with furniture of office spaces.
Keywords: design; strategic planning; concept; function; organization; furnishing; office space; furniture; material